Situating household management of children's asthma in the context of social, economic, and environmental injustice. (2nd January 2022) - Hunleth, Jean; Spray, Julie; Ruiz, Sienna; Maki, Julia; Fedele, David A.; Prabhakaran, Sreekala; Forsyth, Rachel B.; Sykes, Cassidy; Crepps, Kaylah; Shepperd, James; Bowen, Deb; Waters, Erika A.
Abstract: Background: Structural determinants of health are social, economic, and environmental forces that generate unequal opportunities for resources and unequally distribute exposure to risk. For example, economic constraint, racial discrimination and segregation, and environmental injustice shape population-level asthma prevalence and severity. Structural determinants are especially relevant to consider in clinical settings because they affect everyday household asthma management. Objective: To examine how structural determinants shape everyday household management of pediatric asthma and offer a framework for providers to understand asthma management in social context. Design: Qualitative interviews of caregivers for children with asthma. Participants: Participants included 41 caregivers in two U.S. cities: St. Louis, Missouri ( n  = 25) and Gainesville, Florida ( n  = 16). Most caregivers were women (83%), Black (73%) and/or had low socioeconomic status (SES; 78%). Caregivers cared for children with asthma aged 0–4 (32%), 5–11 (68%) and 12–17 (54%). Approach: We carried out narrative interviews with caregivers using an adapted McGill Illness Narrative Interview and using qualitative analysis techniques (e.g. inductive and deductive coding, constant comparison). Key Results: Caregivers highlighted three ways that structural determinants complicated asthma management at home: 1) housing situations, 2) competing household illnesses and issues, and 3) multi-household care. Conclusions: By connecting social, economic, and environmental injustices to the everyday circumstances of asthma management, our study can help providers understand how social contexts challenge asthma management and can open conversations about barriers to adherence and strategies for supporting asthma management at home. We offer recommendations for medical system reform, clinical interactions, and policy advocacy.